Comparison of depressive disorders between the mothers of children with and without autism spectrum disorder (Bangladesh Journal of Psychiatry, 2020)
Autism spectrum disorder (ASD) is a neuro-developmental disorder and a lifelong condition which has considerable impact on parents. Various psychiatric conditions are common in mothers of ASD children including depression, anxiety, low self-esteem, feeling of social isolation and high social anxiety. The objective of the study was to evaluate the presence of depression in mothers of ASD children in comparison with mothers of normally developing children. This was a cross-sectional, comparative and analytical study carried out in the outpatient department of Psychiatry in collaboration with the Shishu Bikash Kendro of Sylhet MAG Osmani Medical College Hospital Sylhet, Bangladesh during the period from 1st January 2015 to 31st December 2015. A total of 75 mothers of ASD children were selected by convenient sampling technique and grouped as group A. Another 75 age matched mothers of normally developing children were recruited and grouped as group B. Depression was assessed primarily by using the Beck Depression Inventory (BDI). Those who scored 10 or above points, were evaluated further by mental state examination and DSM 5 criteria. The results showed that, depressive disorder was present in 31 (41.3%) mothers of ASD children and 12 (16.0%) mothers of normally developing children. Significantly higher rate of depressive disorder was present in mothers of ASD children than that of mothers of normally developing children (p=0.001). These findings concluded that the proportion of depressive disorders was higher and statistically significant.Bang J Psychiatry December 2017; 31(2): 32-37